KAMPUNG PENDIDIKAN DAN UPAYA MENSUKSESKAN PROGRAM WAJIB BELAJAR 12 TAHUN - Khusnan Iskandar; Saeful Anam (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
Abstract: This research article discusses the education village and the effort to make the 12- year study program successful in Lowayu Dukun Gresik. The participation of society in the development of the village community education is the main assets the development progress of the Indonesian state. Education will be able to advance with the support of all elements that are conceptualized in the center of education (schools, families and environment). This research is field research with a qualitative-phenomenological approach. The analysis process is carried out by means of data reduction, data display, and conclusion. The results of this study indicate that first, the foundation in developing educational villages in Lowayu Gresik is a juridical foundation (Pancasila, UUD 1945, PP No. 20 of 2003) philosophical foundation with reference to the flow of empiricism, the foundation of religion by making the Qur'an and al-hadith as the basis, then the psychological foundation and sociological foundation. Second, the construction of village education development application is done by involving the society as a major aspect for success, using the humanistic approach, and the pattern of community-based education as the design of the development of an educational village. Third, results of the development of this educational village can be proud of, because the awareness of children and parents and the community began to develop. In addition, the target for the success of the compulsory education program has been fulfilled where there are no school dropouts found in the village.Keyword: Village, education